Consumptive and non‐consumptive effects of wolf spiders on cotton bollworms. Issue 2 (6th January 2016) - Rendon, Dalila; Whitehouse, Mary E.A.; Taylor, Phillip W.
Abstract: Larvae of the cotton bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) that survive on genetically modified Bt cotton ( Gossypium hirsutum L., Malvaceae) contribute to the risk of widespread resistance to Bt toxins. Current resistance management techniques include pupae busting, which involves deep tilling of the soil to kill overwintering pupae. Unfortunately, pupae busting runs counter to soil and water conserving techniques, such as minimum tillage. This problem could be relieved with biological control methods, whereby predators attack either larvae going to ground to pupate or moths emerging from the ground. We found that the wolf spider Tasmanicosa leuckartii (Thorell) (Araneae: Lycosidae), a common inhabitant of Australian cotton agroecosystems, is an effective predator of H. armigera, attacking and killing most larvae (66%) and emerging moths (77%) in simple laboratory arenas. Tasmanicosa leuckartii also reduced the number of emerging moths by 66% on average in more structurally complex glasshouse arenas. Males, females, and late‐instar juveniles of T. leuckartii were similarly effective. Tasmanicosa leuckartii also imposed non‐consumptive effects on H. armigera, as when a spider was present larvae in the laboratory areas spent less time on the cotton boll and more time on the soil and more mass was lost from the cotton boll. Increased loss of boll mass likely reflects changes in H. armigera foraging behavior induced by the presence of spiders (indirect non‐consumptive effects). Helicoverpa armigera spent more time as pupae when the spider was present in simple laboratory arenas, but not in more complex glasshouse enclosures. Overall, results indicate that T. leuckartii spiders can be effective predators of H. armigera late instars and moths but also suggest that, under some conditions, the presence of spiders could increase the damage to individual cotton bolls.